Effect of chilled air on tool wear and workpiece quality during milling of carbon ﬁbre-reinforced plastic - Muhamad Khairussaleh, Nor Khairusshima; C.H., Che Hassan; A.G. , Jaharah; A.K.M., Nurul Amin; A.N., Md Idriss (Elsevier BV, 2013)
Carbon fibre reinforced plastic (CFRP) is a composite which has the best strength to weight ratio among the construction materials. It becomes valuable as the demand for this composite has increased dramatically especially in automobile and aerospace industry. The need in these industries such as light weight, but retain high strength, make CFRP better choice than steel. CFRP is also known as an expensive material, since an expensive chemical treatment is required in the fabrication process. Therefore, the manufacturing cost of CFRPs’ parts need to be minimized, the factors that influenced the end product’s surface quality such as cost of severe tool wear, which shortens the tool life, fibre pull-out and delamination of CFRP need to be eliminated. Many studies on tool geometries, cutting tool materials, and cutting parameters have been done to overcome these problems. In this study, chilled air of −10 °C was applied to the cutting tool using a vortex tube, which is new in the machining of fibres, to minimize the heat generated during machining. Cutting speed of 160–200 m/min and a feed rate of 0.025–0.05 mm/rev on solid uncoated carbide during the milling process were discussed. At room temperature conditions, it is observed that the wear area is found polished and shining. Under room temperature cutting condition, the wear region is high at higher cutting speeds and feed rates, but in chilled air machining, these types of wear of the carbide tool are found less at higher cutting speeds and feed rates. The improvement in tool life while applying chilled air during machining of CFRP is 1.6% and 12.1% at lowest feed rate and cutting speed; while 31.8% and 45.6% longer tool life of carbide cutting tool is observed at highest feed rate and cutting speed under chilled air machining compared to room temperature machining. The delamination factor of CFRP is also found to improve at higher cutting speeds during chilled-air machining.